Muscle quality index correlates with arthritis: a cross-sectional study from NHANES 2011–2014 - Wang, Chao; Xu, Haotai; Wang, Lei; Huang, Sidan; Pan, Bingcheng; Pan, Hui; Jia, Haisheng; Tang, Shujie (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to investigate the association between Muscle Quality Index (MQI) and arthritis using data from the National Health and Nutrition Examination Survey (NHANES) 2011–2014.MethodsA cross-sectional analysis was conducted using data from 4,558 participants aged 20–60 years. MQI was calculated using handgrip strength and appendicular skeletal muscle mass obtained through Dual-energy X-ray Absorptiometry (DXA) scans. Arthritis status was determined based on self-reported physician diagnoses. Multivariable logistic regression models were applied to examine the relationship between MQI and arthritis, adjusting for potential confounders, including demographic, socioeconomic, and lifestyle factors. Subgroup and sensitivity analyses were performed to evaluate heterogeneity.ResultsHigher MQI was significantly associated with a lower risk of arthritis (adjusted OR = 0.73, 95% CI: 0.61–0.88, P = 0.001). Subgroup analyses revealed stronger associations in participants aged 30–40 years (OR = 0.47, 95% CI: 0.31–0.71, P < 0.001), females (OR = 0.68, 95% CI: 0.54–0.87, P = 0.002), and non-hispanic black people individuals (OR = 0.62, 95% CI: 0.43–0.89, P < 0.01). Sensitivity analysis confirmed a dose-response relationship, with participants in the highest MQI quartile having significantly lower odds of arthritis compared to the lowest quartile (adjusted OR = 0.69, 95% CI: 0.50–0.96, P = 0.027).ConclusionsMQI is inversely associated with arthritis prevalence, suggesting that maintaining muscle quality may be a critical factor in arthritis prevention. These findings highlight the importance of muscle health in public health strategies for arthritis management.